Analysis of passivity problems in the baltic equity market - Belovas, Igoris; Kabašinskas, Audrius; Sakalauskas, Leonidas (Lietuvos matematikos rinkinys, 2023)
The Baltic States equity market is a challenge for investors and financial analysts. Unfortunately strong assivity is observed in ``young’’ markets, therefore any (Gaussian, α-stable etc) distribution fitting tests (Anderson–Darling, Kolmogorov–Smirnov, etc.) are poorly applicable. Improvement based on mixed distributions is proposed and its adequacy in the Baltic States market is tested. In this paper we use Koutrouvelis goodness-of-fit test and modified χ2 test.